Technology and labor regulations - Alesina, Alberto 1957-2020; Zeira, Joseph (National Bureau of Economic Research, 2006)
Many low skilled jobs have been substituted away for machines in Europe, or eliminated, much more so than in the US, while technological progress at the "top," i.e., at the high-tech sector, is faster in the US than in Europe. This paper suggests that the main difference between Europe and the US in this respect is their different labor market policies. European countries reduce wage flexibility and inequality through a host of labor market regulations, like binding minimum-wage laws, permanent unemployment subsidies, firing costs, etc. Such policies create incentives to develop and adopt labor-saving capital intensive technologies at the low end of the skill distribution. At the same time technical progress in the US is more skill biased than in Europe, since American skilled wages are higher.
Literaturverz. S. 31 - 33